Formulasi Ikan Nila (Oreochromis niloticus) dan Daun Binahong (Anredera scandens (L.) Moq.) pada Pembuatan Pasta Fetucini - Khumaidi Khumaidi; Esteria Priyanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The development of fettuccine pasta products with the addition of tilapia and binahong leaves aims to find the composition of the ingredients of fettuccine pasta that is preferred and well accepted by the panelists. The methods used are experimental method and hedonic test. The experiment of making fettuccine pasta with the addition of tilapia and binahong leaves used a formulation with 3 treatments, namely F1 for the addition of 15 g of tilapia and 35 g of binahong leaves, F2 for the addition of 10 g of tilapia and 40 g of binahong leaves, and F3 for the addition of 5 g of tilapia and 45 g of binahong leaves. The hedonic test involved 25 semi-trained panelists. The results showed that fettuccine pasta with the addition of 15 g of tilapia and 35 g of binahong leaves was the most preferred product and was well accepted by the semi-trained panelists. The composition of the ingredients of the substituted fettuccine pasta with tilapia and binahong leaves that had the best acceptance included 200 g of semolina flour, 15 g of tilapia, 35 g of binahong leaves, 180 g of chicken eggs, 1 tsp of salt, and 1 tsp of olive oil.